Radiation field creation at the electron linac LUE-10 for long-term tests of structural materials under molten-salt reactor conditions - Dovbnya, A.N.; Zykov, A.I.; Zlunitsyn, Eh.S.; Torgovkin, A.V.; Shramenko, B.I. (Вопросы атомной науки и техники, 2006)
Long-term (700 hours) corrosion tests of hastelloy-type alloy samples were performed in the ZrF4+NaF melt at a temperature of 650°C with the use of the electron linac LUE-10 of power of about 5 kW. To reduce the residual radioactivity of irradiated materials, studies were made into possible ways of a smooth energy shift at the maximum of the electron spectrum to the lower energy region under conditions of a strong current load.